Gradientes de diversidade de vespas e abelhas (Hymenoptera: Aculeata) em campos rupestres da Cadeia do Espinhaço - Lucas Neves Perillo (2017)
Understanding spatial-temporal patterns and mechanisms that determine the distribution of wasps and bees fauna (Aculeata) associated with the campo rupestre of Cadeia do Espinhaço, an important Brazilian mountain range, was the main objective of this thesis, using different scales and approaches. In the first chapter, we shown that the geographic distance caused by the altitudinal variation is important for community structure, especially considering species turnover as a fundamental mechanism for the maintenance of beta diversity. In the second chapter, we questioned the existence of seasonality in wasps and bees communities associated with natural fragments of Atlantic forest, and whether landscape metrics influence this temporal species dynamic. We found an effect of seasonality on species richness and showed that temporal species turnover increases with continuous forest distance (the only metric that influenced species richness, abundance or composition). In the last chapter, we defined sample points at the base (around 1100m.a.s.l.) and near mountain summit (ranging from 1400 to 2000m.a.s.l.) in twelve locations along Cadeia do Espinhaço, in order to understand distribution patterns of wasps and bees along their latitudinal and altitudinal gradient and how climate variables influences it at different diversity scales. In this context, we found that altitude is more important than latitude in determining α and γ diversities, with temperature being the main climate mechanism to explain these patterns.